Assessment of nurses' cardiopulmonary resuscitation knowledge and skills within three district hospitals in Botswana - Lakshmi Rajeswaran; Megan Cox; Stoffel Moeng; Billy M. Tsima (AOSIS, 2018)
Background: Nurses are usually the first to identify the need for and initiate cardiopulmonary resuscitation (CPR) on patients with cardiopulmonary arrest in the hospital setting. Cardiopulmonary resuscitation has been shown to reduce in-hospital deaths when received from adequately trained health care professionals. Aim: We aimed to investigate nurses' retention of CPR knowledge and skills at district hospitals in Botswana. Methods: A quantitative, quasi-experimental study was conducted at three hospitals in Botswana. A pre-test, intervention, post-test, and a re-test after 6 months were utilised to determine the retention of CPR knowledge and skills. Non-probability, convenience sampling technique was used to select 154 nurses. The sequences of the test were consistent with the American Heart Association's 2010 basic life support (BLS) guidelines for health care providers. Data were analysed to compare performance over time. Results: This study showed markedly deficient CPR knowledge and skills among registered nurses in the three district hospitals. The pre-test knowledge average score (48%) indicated that the nurses did not know the majority of the BLS steps. Only 85 nurses participated in the re-evaluation test at 6 months. While a 26.4% increase was observed in the immediate post-test score compared with the pre-test, the performance of the available participants dropped by 14.5% in the re-test 6 months after the post-test. Conclusion: Poor CPR knowledge and skills among registered nurses may impede the survival and management of cardiac arrest victims. Employers and nursing professional bodies in Botswana should encourage and monitor regular CPR refresher courses.